System robustness analysis in support of flood and drought risk management - Mens, M. J. P. (Deltares select series, 2015)
Floods and droughts have an increasing impact on societies worldwide. It is unlikely that the provision of flood protection infrastructure and reservoirs will eliminate this problem, especially as extreme events are expected to increase in probability and magnitude as a result of climate change. For this reason, the focus of water management has shifted to a risk-based approach in recent years; but this also has its limitations.This book examines system robustness as a new perspective on flood and drought risk management. The concept of robustness is familiar from other areas, such as engineering and biology. When a system is robust, it can remain functioning even when some components fail. Areas prone to flooding or drought can be understood as systems, and this book makes the concept of robustness operational by proposing quantifiable criteria. These criteria were tested in two case studies of flooding and two of drought, which demonstrate the applicability of the framework and provide insight into the system characteristics that influence system robustness. The book will contribute to decision-making in flood and drought risk management by providing additional decision criteria, and will be of interest to all those whose work involves the management of disastrous and uncertain flood and drought events.